QUILLBOT Y SU APORTE EN EL APRENDIZAJE DE LOS ESTUDIANTES DE LA CARRERA DE PEDAGOGÍA DE LAS CIENCIAS EXPERIMENTALES INFORMÁTICA, SECCIÓN MATUTINA DE LA UNIVERSIDAD TÉCNICA DE BABAHOYO, PERIODO ACADÉMICO ABRIL- AGOSTO 2024. - MUÑOZ ARROYO MAIROVEN DENISSE (2024)
The study "Quillbot and its impact on the learning of Pedagogy of Experimental Sciences and Computer Science students, morning section of the Technical University of Babahoyo, April-August 2024" seeks to evaluate how Quillbot influences the preparation of academic texts. Using a quantitative approach, a survey was conducted among PCEI students to analyze the effectiveness of the tool. The methodology includes exploratory and descriptive approaches: the former examines understudied phenomena and the latter details specific characteristics. Deductive and analytical-synthetic methods were used, along with documentary research techniques and surveys with a sample of 75 students. The results reveal that students face significant difficulties in the organization and structure of their texts, affecting their ability to meet academic standards. It is recommended to offer workshops on textual organization, argumentation, and training in the use of Quillbot to improve academic writing and student achievement.